Bacterial and parasiter agents in the obliterated sheep livers and their economical losses in Elazi? slaugterhouse - Özer, Edip; Özcan, Celal; Arslan, Nurcan; Kalender, Hakan; Angin, Muhammet (Scientific and Technical Research Council of Turkey, 1996)
Livers of 6235 sheep slaughtered at Elazi? Slaughterhouse between September 1992 and August 1993 were inspected for the presence of parasites and abscesses. Parasite infestation alone, abscesses alone and both parasites and abscesses together were observed in 825 (62.97%). 196 (14.96%) and 289 (22.06%) livers, respectively. After the inspections, these livers were partially or completely destroyed. Overall Destruction rates were 37.26% in the fall 20.40% in the winter, 9.64% in the spring and 12.97% in the summer. Infestation rates for Fasciola hepatica. Dicrocoelium dendriticum. Cyste hydatique and Cysticercus tenuicollis in 1114 with parasites were 16.01, 45.69, 62.65 and 2.76% respectively. In 121 livers which contained either abscesses alone or abcessus and parasites, bacteriological examinations indicated that in 17 livers (14.05%). no bacteriological agent was detected. In the remaining 104 livers, Staphylococcus aureus (43.26%) and Escherichia coli (36.53%). were the most frequently isolated bacteria. Other bacterial species isolated were Corynebacterium pseudotuberculosis (19.23%). Corynebacterium pyogenes (10.57%). Fusobacterium necrophorum (6.73%), Camphylobactercoli(1.99%). Salmonella Spp. (1.99%), Psedomonas aeruginosa (0.96%), Listeria spp. (0.96%). Pasteurella haemolytica (0.96%), Bacillus spp. (0.96%), Streptococcus pyogenes (2.88%). Citrobacter freundi (2.88%). Clostridium oedematiens (8.65%) and Cl. perfringens (3.84%). In 45 livers which only had abscesses. Cl. perfringenes. Cl. oedemations, C. freundi and Bacillus spp. species were not isolated. In 59 livers with both parasites and abscesses, F. necrophorum. C. coli. PS. aeruginosa, Listeria spp. and P. haemolytica were not present. Partially or completly destroyed livers for abscesses or for parasites weighed 964 kg. the economical losses of the slaughterhouse, according to the unit meat prices at the time of destruction was 25.546.000 Turkish liras.
Elazi? Et ve Balik Kurumunda Atilan Koyun Karaci?erlerinde Bakteriyel ve Paraziter Etkenlerle Bunlarin Oluşturdu?u Ekonomik Kayiplar
Keywords: Bacteria; Economical losses; Parasite; Sheep